Breakup and coalescence of large and small bubbles in sudden expansions and contractions in vertical pipes. (April 2021) - Celis, G.E.O.; Rosero, C.M.P.; Loureiro, J.B.R.; Silva Freire, A.P.
Highlights: Results for the mean velocity profiles, local shear rate and turbulent kinetic energy are presented. Size and velocity distributions for small and long bubbles are discussed. Measured data are compared with existing theories for the motion of small and large confined bubbles. Bubble breakup and coalescence are ruled by the dynamic pressure forces of the turbulent motions. The formation of a gas pocket in the contraction is an important promoter of bubble breakup. Abstract: The present work studies the dynamics of large and small bubbles in sudden expansions and contractions in vertical pipes. The experimental apparatus was designed to permit changes in flow patterns through singularities provoked by an expansion followed by a contraction. The data were obtained through particle image velocimetry and the shadow sizer technique. Size and velocity distributions for small and long bubbles are presented for six vertical pipe positions and compared with existing theories for the motion of small and large confined bubbles. Results for the mean velocity profiles, local shear rate and turbulent kinetic energy of the continuous phase are also presented. Predictions on the permissible largest diameter of bubbles as a function of space coordinates and flow conditions based on phenomenological theories are compared with the experimental data. Results indicate that bubble breakup and coalescence are essentially ruled by the dynamic pressure forces of the turbulent motions, but shear induced breakup is also observed for the small and large bubbles. The formation of a gas pocket in the contraction is identified as an important promoter of bubble breakup.